Killing Jesus [compact disc, unabridged] : a history - O'Reilly, Bill (Macmillan Audio, 2013)
The anchor of The O'Reilly Factor details the events leading up to the murder of one of the most influential men in history: Jesus of Nazareth. Nearly 2,000 years after this controversial young revolutionary was crucified, more than 2.2 billion human beings attempt to follow his teachings and believe he is God. Killing Jesus will take listeners inside Jesus' life, recounting the seismic political and historical events that made his death inevitable and changed the world forever.